(untitled) (Revista Argentina de Musicología, 2018)
In this paper we will try to outline some points of con1act between music and philosophy. Taking a starting point in what we call the fall of the western modem ideal, we propose an approach to the notion of "deconstruction", examining some works of New Musicology literature and others where we can read the "detractors" points of view on this new perspective of musical thought. The article seeks to establish the pertinence of the use of "deconstruction" as a key to understand the New Musicology perspective, taking into account the kind of work that idea involves in Jacques Derrida.